A STUDY OF THE AMORPHIZATION REACTION IN NI-ZR MULTILAYERS BY NEUTRON REFLECTOMETRY - Zarbakhsh, A; Cowlam, N; Highmore, R; Evetts, J; Penfold, J; Shackleton, C (1990)
The critical neutron spectrometer, CRISP, at the ISIS pulsed neutron source at the Rutherford Appleton Laboratory has been used for an in situ study of the solid-state amorphisation reaction in sputtered multilayer Ni-Zr thin films heated to 235 degrees C in air. The variation of neutron reflectivity with wavelength observed for the samples shows very clearly a structure which changes during the reaction. This illustrates the considerable potential of the neutron reflectivity method.